2020
DOI: 10.1158/1078-0432.ccr-20-0397
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a RAS-activating TMEM87A–RASGRF1 Fusion in an Exceptional Responder to Sunitinib with Non–Small Cell Lung Cancer

Abstract: and Mirati Therapeutics; and receives post-marketing royalties from DFCI owned intellectual property on EGFR mutations licensed to Lab Corp.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 26 publications
(28 reference statements)
0
19
0
Order By: Relevance
“…Despite the presence of fusions involving established oncogenes including ABL1 , JAK2 , or FGFR2 with different partner genes, and RET -intergenic fusion, these patients maintained disease control with EGFR-TKIs for more than 2 years, suggesting that fusions with these known oncogenes did not lead to clinical drug resistance. To understand this discrepancy and to establish the clinical significance of putative fusions in patients who have not undergone EGFR-TKI treatment, including case #3 with putative FGFR1 fusion, we performed bulk RNA-sequencing, followed by bioinformatic analyses – this approach previously led us to discover an unknown oncogenic fusion 15 .
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the presence of fusions involving established oncogenes including ABL1 , JAK2 , or FGFR2 with different partner genes, and RET -intergenic fusion, these patients maintained disease control with EGFR-TKIs for more than 2 years, suggesting that fusions with these known oncogenes did not lead to clinical drug resistance. To understand this discrepancy and to establish the clinical significance of putative fusions in patients who have not undergone EGFR-TKI treatment, including case #3 with putative FGFR1 fusion, we performed bulk RNA-sequencing, followed by bioinformatic analyses – this approach previously led us to discover an unknown oncogenic fusion 15 .
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…RNA-based targeted NGS can detect unknown fusions only in cases where the specific exons of at least the 5′ or 3′ genes have been pre-designed 14 . However, we have recently shown that bulk RNA sequencing (RNA-seq) offers an unbiased genome-wide method to identify oncogenic fusions that are missed by hybrid capture NGS 15 .…”
Section: Introductionmentioning
confidence: 99%
“…17 However, there were no clinical or pathology details nor descriptions of the fusion partner gene. 17 Regarding RASGRF1-fused tumors described outside of the skin, only acute myeloid leukemia with a TMEM154:: RASGRF1 fusion 23 and a non-small cell lung cancer with TMEM87A::RASGRF1 fusion 24 have been so far reported. This underscores the overall scarcity of data regarding RASGRF1-fused neoplasms.…”
Section: Discussionmentioning
confidence: 99%
“…TMEM87A and TMEM87B have been associated with protein transport to and from the Golgi, mechanosensitive cation channel activity, and cardiac and other developmental processes 25 . In humans, TMEM87 proteins have been implicated in developmental diseases and cancers 69 .…”
Section: Introductionmentioning
confidence: 99%
“…In a patient with a severe cardiac phenotype, whole-exome sequencing uncovered a paternally inherited TMEM87B missense mutation and chromosome 2 deletion inherited from an unaffected mother 8 . Both TMEM87A and TMEM87B have additionally been implicated in cancers such as non-small cell lung cancer through fusion or suspected interaction with oncogenes 6,7,10 .…”
Section: Introductionmentioning
confidence: 99%